Pelatihan Hasil Olahan Laut oleh Tim KKNT untuk Meningkatkan Ekonomi Kreatif Masyarakat Desa Padelegan - Nifa, Maulidia; Rahmawati, Ika Dian; A'yun, Dya Qurotul; Ningsih, Puji Rahayu (Jurnal Solutif: Jurnal Pengabdian Masyarakat, 2025)
The marine products training carried out by the Thematic Real Work Lecture Team (KKNT) in Padelegan Village aims to improve the community's creative economy through processing marine products. By utilizing the potential of abundant marine resources, this training provides knowledge and skills to the community in processing marine catches into value-added products, such as fish crackers, dimsum and meatballs. The training methods used include coordination, discussion, activity planning and training which allows participants to be directly involved in the product manufacturing process. The results of the training showed significant improvements in processing skills and understanding of hygiene and sanitation practices. Apart from that, this program also encourages the formation of small businesses based on processed seafood, which has the potential to increase people's income. Continuous support from various parties is needed to ensure the sustainability of the businesses that have been built. Thus, this training not only contributes to improving the local economy but also strengthens the independence of the Padelegan Village community in managing their marine resources